Desain dan Implementasi Film Viewer X-Ray Berbasis Sensor Detektor Untuk Visualisasi Gambar Radiografi - Suwarmiyati; Soekarman; Hasmah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
X-Ray film is a medium used to capture body organ shadows using X-ray exposure. This study designed and implemented a portable X-Ray film viewer device equipped with an optocoupler sensor for film detection and adjustable light intensity. The system uses an Arduino Uno microcontroller and battery power supply, making the tool mobile and practical. The test results showed a standard deviation of 0.4 with an uncertainty of 0.2 and an average deviation of 0.10. The device is declared feasible to assist medical personnel in reading X-Ray films effectively and efficiently